2023
DOI: 10.2174/1874467215666220928110557
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Shogaol in Metals (Al, As and Pb) and High-fat diet-induced Neuroinflammation and Behavior in Mice

Abstract: Background: Increased exposure of humans to toxic metals and high fat diet (HFD) consumption severely damages brain health. Natural plant extracts have shown huge potential to treat multiple human diseases. Objective: The present study was designed to evaluate the protective effects of Shogaol (an active component of ginger) in neuroinflammation and behavioral paradigms in mice treated with metals and HFD. Methods: 8-11 weeks old male mice model was developed by giving a combination of metals i.e. Arsenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 163 publications
0
3
0
Order By: Relevance
“…Gingerol is the main pungent compound in fresh ginger, while ginger phenol is formed during heating or cooking of ginger, and 6-SH is the most abundant gingerol analogue in dry ginger [42] . Studies have shown that 6-SH exerts neuroprotective effects by inhibiting neuroin ammation [43][44][45] , suggesting its potential as a neuroprotective agent. Research by Nazim UM et al found that 6-SH treatment increases p62 expression and decreases LC3 expression levels, inhibiting autophagic ux, inhibiting tumor cell proliferation, and inducing TRAIL-mediated cell death in liver cancer cells [46] .…”
Section: Discussionmentioning
confidence: 99%
“…Gingerol is the main pungent compound in fresh ginger, while ginger phenol is formed during heating or cooking of ginger, and 6-SH is the most abundant gingerol analogue in dry ginger [42] . Studies have shown that 6-SH exerts neuroprotective effects by inhibiting neuroin ammation [43][44][45] , suggesting its potential as a neuroprotective agent. Research by Nazim UM et al found that 6-SH treatment increases p62 expression and decreases LC3 expression levels, inhibiting autophagic ux, inhibiting tumor cell proliferation, and inducing TRAIL-mediated cell death in liver cancer cells [46] .…”
Section: Discussionmentioning
confidence: 99%
“…are the most popular spices worldwide, especially in Asian countries, and have many distinct bioactive compounds with antiinflammatory and antioxidant properties (Ran et al, 2019). Ginger and its bioactive components, such as zerumbone, curcumin, 6-gingerol, and shokol, have been reported to enhance learning and memory in animal models (Adetuyi & Farombi, 2021;Arcusa et al, 2022;Ishaq et al, 2022;Kim et al, 2010Kim et al, , 2018Liu et al, 2019;Talebi et al, 2021;Zarei et al, 2021). Some reports have suggested that ginger extract can alleviate cognitive deficits by regulating ERK/CREB activation or inhibiting nitric oxide production (Lim et al, 2014;Mustafa et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…At present, population-based studies have reported well-established positive correlations between blood/dentine Pb levels and anxiety in children. , However, most current studies in animal experiments remain at the level of validity of this relationship, , with sparse information regarding underlying neural mechanisms. A number of molecular studies have been performed to characterize the mechanisms and a few of differentially expressed molecules are identified. However, these molecules are involved in multiple areas of research and none of them have been proven to have a role in Pb-induced anxiety and depression, making it difficult to precisely identify the research direction for us. On the other hand, behaviors can be more directly regulated by neuronal activity than molecules.…”
Section: Introductionmentioning
confidence: 99%